Night shift work and other determinants of estradiol, testosterone, and dehydroepiandrosterone sulfate among middle-aged nurses and midwives - Beata Peplonska; Agnieszka Bukowska; Jenny Anne Lie; Jolanta Gromadzińska; Shanbeh Zienolddiny (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: The aims of our study were to (i) investigate the association between rotating night shift work and blood concentrations of estradiol, testosterone and dehydroepiandrosterone sulfate (DHEAS) and (2) evaluate the role of their non-occupational determinants. METHODS: A cross-sectional study was conducted on 345 premenopausal and 187 postmenopausal nurses and midwives (263 women working rotating night shifts and 269 women working during days). Data from in-person interviews were used, anthropometric measurements were performed, and body mass index (BMI) and waist- to-hip ratio were calculated. Morning blood and spot urine samples were collected. Multiple linear regression models were fitted with hormone concentrations as dependent variables, and night shift work characteristics and demographic, reproductive, lifestyle and anthropometric determinants as independent variables. Modification of the effect by chronotype was examined. RESULTS: Among postmenopausal women, we observed a statistically significant positive association between the total duration of night shift work >15 years and estradiol level (P<0.05 when compared to night work duration <5 years). Night shift work characteristics were significantly associated with estradiol among morning-type postmenopausal women. The well-established associations between hormones and their major determinants, such as age and BMI, were confirmed. CONCLUSIONS: The findings of our study imply that prolonged night shift work may be associated with increased estradiol levels among postmenopausal women, especially among the morning-type postmenopausal women.